The mathematical model and the method of optimal stochastic control over the modes of the water main operation - Тевяшев, Андрей Дмитриевич; Матвиенко, Ольга Ивановна (Eastern-European Journal of Enterprise Technologies, 2015)
The study is devoted to the problem of increasing the efficiency of water mains in the present circumstances of transition to the three-band electricity tariffs. We have devised a new class of optimal stochastic discrete-time control over complex dynamic objects that is distinguished by additional extreme and probabilistic constraints on the phase variables. The suggested mathematical formulation of the optimal stochastic control over the modes of the water main has probabilistic constraints on the phase variables. We have also proposed a new strategy for the optimal stochastic control over the modes of the water main. The strategy takes into account the specific features of the water main as an object of stochastic control that operates in a stochastic environment, which allowed devising an effective method to solve the problem. It is shown that transition from the classic deterministic tasks of control over the modes of water mains to stochastic problems ensures a much lower (up to 9 %) electricity cost.